2022
DOI: 10.3390/su14137599
|View full text |Cite
|
Sign up to set email alerts
|

External Monitoring, ESG, and Information Content of Discretionary Accruals

Abstract: Discretionary accruals reflect the management’s accounting choices made within the flexibility of accounting standards. Discretionary accruals can be used by the management to better reflect the economic value of the firm and to signal their private information about a firm’s future prospects to the market, but they can also be used opportunistically by managers. However, the prior literature documents mixed evidence related to the information content in discretionary accruals. Thus, we examine the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
2
1
Order By: Relevance
“…Some studies used the modified Jones model (1995) and have an R 2 larger than this study, for example, Amar (2014) reported R 2 68%. However, another study reported an R 2 of less than 25% (Hong et al , 2022), which is less than that reported in this study. The result in Model 2 has an R 2 of 64.1% and an F -statistic of 73.26 at a 1% significance level.…”
Section: Empirical Results and Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Some studies used the modified Jones model (1995) and have an R 2 larger than this study, for example, Amar (2014) reported R 2 68%. However, another study reported an R 2 of less than 25% (Hong et al , 2022), which is less than that reported in this study. The result in Model 2 has an R 2 of 64.1% and an F -statistic of 73.26 at a 1% significance level.…”
Section: Empirical Results and Discussioncontrasting
confidence: 92%
“…To determine the value of DAC, this study uses the model below on the ACMD and FOWN as a moderating variable. The absolute value of DAC is better to measure the EM, as this proxy combined both income-decreasing and income-increasing (Hong et al, 2022). Controlling variables are AC size, AC independence, AC expertise, firm age, firm size and leverage; in addition to the year dummy and industry dummy, the model can be specified as follows: This study used the cash flow method to estimate total accruals.…”
Section: Regression Model Specificationmentioning
confidence: 99%
“…To facilitate as much separation between relevance and reliability as possible, we constructed a measure that acknowledges five observable indicators suggesting impaired reliability. Notably, ample literature detects earnings management using discretionary accruals (e.g., [12][13][14][15][16][17][18][19][20]). However, accrual metrics do not allow measurement of reliability apart from relevance because accruals are value-relevant accounting information.…”
Section: Measuring Reliabilitymentioning
confidence: 99%